2020
DOI: 10.1016/j.dsx.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Relation of D-dimer levels of COVID-19 patients with diabetes mellitus

Abstract: Background and aims Diabetes is a frequent comorbidity in patients with Severe COVID-19 infection associated with a worse prognosis. Hypercoagulability with elevation in D-dimer levels has been demonstrated in patients with COVID-19. This study aims to study D-dimer levels in people with diabetes compared to those without diabetes among patients with COVID-19 infection. Methods In this observational study 98 moderate and severely ill patients with COVID-19 infection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
49
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 12 publications
7
49
0
3
Order By: Relevance
“…The median D-dimer level in diabetic was found to be 1.68 μg/ml. In a recent publication, Mishra et al have reported an association of diabetes with increased D-dimer levels in moderately sick COVID 19 patients [ 20 ]. Similar to our study, in their study also peak D-dimer levels during the entire course of hospital stay were utilized in statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The median D-dimer level in diabetic was found to be 1.68 μg/ml. In a recent publication, Mishra et al have reported an association of diabetes with increased D-dimer levels in moderately sick COVID 19 patients [ 20 ]. Similar to our study, in their study also peak D-dimer levels during the entire course of hospital stay were utilized in statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer values are even higher in patients with severe COVID-19 than in those with milder forms and therefore, D-dimer measurement may be associated with evolution toward worse clinical picture in COVID-19 patients. [26][27][28][29][30] Notably, Tang et al also recently highlighted that the vast majority of COVID-19 patients who died during hospital stay fulfilled the criteria for diagnosing disseminated intravascular coagulation (71.6 versus 0.6% in survivors). In the present study mean D-dimer values reduced significanctly in all subjects at the end of therapy (EOT) and it was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of several biomarkers has been suggested to assess/monitor the severity of the disease in these patients. Interestingly, in patients with hyperglycemia and COVID-19 increased D-dimer levels have been found [ 163 , 164 ]. Quin et al, reported that elevated levels of D-Dimer (OR: 1.095, 95% CI: 1.045–1.148, p <0.001) in T2D patients were associated with an increased mortality.…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%
“…Most of the clinical studies found in this review compared patients with severe and non-severe symptoms, and survivors vs. non-survivors. By extracting clinical summarized data, various studies showed significant evidence of a systemic reduction in T-cell populations (lymphocytopenia) in obese/T2D patients as COVID-19 progressed [ 134 , 155 , 156 , 158 , 162 , 163 , 164 , 170 ]. Importantly, patients hospitalized with underlying conditions presented worse lymphocytopenia than those who did not report comorbidities [ 178 , 185 , 186 , 187 , 189 ].…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%